2019
DOI: 10.3389/fnins.2019.00313
|View full text |Cite
|
Sign up to set email alerts
|

Excess Folic Acid Supplementation Before and During Pregnancy and Lactation Activates Fos Gene Expression and Alters Behaviors in Male Mouse Offspring

Abstract: Periconceptional folic acid (FA) supplementation is recommended to prevent neural tube defects and other birth defects. After 20 years mandate food fortification with FA, serum concentration of folate and unmetabolized FA increased significantly in the North American population. But whether excess FA intake impairs neurodevelopment and behavior is still controversial. Here, we treated mice with approximately 2.5-fold (moderate dose of FA, MFA) or 10-fold (high dose of FA, HFA) the dietary requirement of FA 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 71 publications
1
44
0
Order By: Relevance
“…Additionally, a marginally significant form effect ( p = 0.054) on ambulatory activity during the light-cycle was found that was largely driven by lower activity in 5X-MTHF compared to the 5X-FA offspring, but similar to 1X offspring; potentially contributing to their higher weight gain [ 41 ]. These results are also consistent with recent reports that show moderately high (5X) dose FA exposure throughout gestation to induce hyperactivity-like behavior in female [ 42 ] and male [ 43 ] offspring post-weaning. The body weight and food intake of the dams during pregnancy and lactation were not different between groups, nor were litter sizes or early-life growth of their offspring.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a marginally significant form effect ( p = 0.054) on ambulatory activity during the light-cycle was found that was largely driven by lower activity in 5X-MTHF compared to the 5X-FA offspring, but similar to 1X offspring; potentially contributing to their higher weight gain [ 41 ]. These results are also consistent with recent reports that show moderately high (5X) dose FA exposure throughout gestation to induce hyperactivity-like behavior in female [ 42 ] and male [ 43 ] offspring post-weaning. The body weight and food intake of the dams during pregnancy and lactation were not different between groups, nor were litter sizes or early-life growth of their offspring.…”
Section: Discussionsupporting
confidence: 93%
“…Similar but less severe deficits were observed in rats exposed to Ab during GST alone or only during the PRW period, suggesting the extreme sensitivity of the fetal as well as the neonatal rat brain to the deleterious effects of exposure to Ab during this period [69]. Chu D et al, (2019) [70] ICR mice Results demonstrated a change in gene expression profile in weaning mice during early life FA supplementation. Long-term behavioral effects were more evident in adult male mouse offspring in a dose-sensitive mode [70].…”
Section: No Treatmentmentioning
confidence: 66%
“…A lower concentration of 5-MTHF in the cell, a reduced transformation to methionine, and an altered methylation process can be the consequences of high concentrations of unmetabolized FA; in this regard, several animal studies have interestingly shown both gene-specific hypermethylation and DNA hypomethylation [77,97,98] in animals fed with higher dosages of FA, and a different grade of modulation of the global DNA methylation has been recently proposed also by Chu et al [70]. Further investigations are, however, requested in humans.…”
Section: Summary Of Evidencementioning
confidence: 89%
See 2 more Smart Citations